2021
DOI: 10.31234/osf.io/5k8de
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Web-based language production experiments: Semantic interference assessment is robust for spoken and typed response modalities

Abstract: For experimental research on language production, temporal precision and high quality of the recorded audio-files are mandatory. These requirements are a considerable challenge if language production is to be investigated online. However, online research has a huge potential regarding efficiency, ecological validity and diversity of study-populations in psycholinguistic and related research, also beyond the current situation. Here, we supply confirmatory evidence that language production can be investigated on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Thus, our initial concern that speech onset latencies would be unreliable turned out to be unwarranted. Other recent studies using internet-based paradigms have provided similar evidence for the reliability of onset latencies, as they replicated several key findings of the speech production literature, including the word frequency effect (Fairs & Strijkers, 2021), the cumulative semantic interference effect (Stark et al, 2021), and the semantic interference effect in the picture-word interference paradigm (Vogt et al, 2021). Fairs and Strijkers (2021) compared the results of their webbased study to those of an otherwise identical study run in the laboratory.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Thus, our initial concern that speech onset latencies would be unreliable turned out to be unwarranted. Other recent studies using internet-based paradigms have provided similar evidence for the reliability of onset latencies, as they replicated several key findings of the speech production literature, including the word frequency effect (Fairs & Strijkers, 2021), the cumulative semantic interference effect (Stark et al, 2021), and the semantic interference effect in the picture-word interference paradigm (Vogt et al, 2021). Fairs and Strijkers (2021) compared the results of their webbased study to those of an otherwise identical study run in the laboratory.…”
Section: Discussionmentioning
confidence: 56%
“…The current study therefore explored the usefulness of dependent measures that did not depend on this synchrony, but were derived from the durations and fluency of the participants' utterances. Meanwhile, recent speech production studies have shown that onset latencies can in fact be measured with good accuracy in web-based platforms (e.g., Fairs & Strijkers, 2021;Stark et al, 2021;Vogt et al, 2021). We review these studies in the Discussion section.…”
Section: Introductionmentioning
confidence: 99%
“…Similar early reassurance came from studies of performance on linguistic tasks such as acceptability judgements (Sprouse, 2011) and self-paced reading (Enochson & Culbertson, 2015). Since then, researchers have extensively explored the validity and reliability of online data collection methods (e.g., see Stark et al, 2022 for recent demonstration of a classic semantic interference effect in word production as measured by key press responses; Angele et al, 2022 for a replication of classic masked priming effects; Ratcliff & Hendrickson, 2021 for exploration of lexical decision data). Importantly, several studies have directly compared the data from the same task when it was performed in the lab using standardized equipment or in participants' own homes with their own hardware.…”
Section: Can We Trust the Data From Online Experiments?mentioning
confidence: 97%